Hoża jako metafora - Karpowicz, Agnieszka (Przestrzenie Teorii, 2024)
The article analyses Paweł Kludkiewicz’s ‘drawn book’ Hoża. My street in the perspective of logovisuality studies. The problem of the relationship between drawing (image) and writing (word) in the context of autobiography is explored, and the relationship of the book’s bi-media form with the transitional crises (of the autobiographical self, the economic one, the pandemic and of the urban space) to which the story refers.